Internet censorship and regulation systems in democracies emerging research and opportunities - Koumartzis, Nikolaos 1984; Veglis, Andreas (Advances in information security, privacy, and ethics (AISPE) book series, 2020)
"This book examines the phenomenon of internet regulation in general, and the use of internet regulation systems by authoritarian regimes and western democracies"